Extinction of Vibrio cholerae in acidic substrata: Contaminated cabbage and lettuce treated with lime juice - Mata, Leonardo (Universidad de Costa Rica, 1994)
Lime juice killed millions of Vibrio cholerae 01, El Tor, Inaba, present on cabbage and lettuce contaminated in the ljiboratory. The lethal effect was evident witbin 5 min of exposure to lime juice. No vibrios could be recovered at dilution 1:10 using alkaline peptone water (APW) and tbiosulfate-citrate-bile salts-saccharose agar (TCBS). Morethan 99.9 % of the initial inoculum was effectively destroyed. The number of vibrios killed by lime juice was 2 to 6 logarithms greater than the maximum infecting dose, and 4 to 8 logs greater than the mínimum infecting dose for cholera El Tor. The time interval needed for killing was smaller than .the usual waiting time for serving food in homes and restaurants. The addition of lime juice to non-acidic foods, beverages and water, is strongly recornmended to prevent infection with cholera vibrios and other acid-sensitive microorganisms. This measure is particularly important for rural and slum populations in the tropics and subtropics.